Overview of the Knowledge of Patients Undergoing Hemodialysis About Continuous Ambulatory Peritoneal Dialysis (CAPD) at RSU Imelda Pekerja Indonesia - Candra Meriani Damanik; Satriani Hartalina Gultom; Ali Asman Harahap; Dedi Alfandi (Cattleya Darmaya Fortuna, 2026)
Hemodialysis is the process of filtering or separating blood from dissolved substances, which in this case are waste products or toxins circulating in the body through the blood, with the assistance of a machine outside the body called a dialysis machine. Chronic Kidney Disease (CKD) is a disorder that occurs in the kidneys and can be caused by various factors. The early onset of this disease generally does not show specific symptoms, making early detection difficult, which often results in patients with kidney failure receiving treatment late. The purpose of this study was to determine the description of knowledge among patients undergoing hemodialysis, to identify Continuous Ambulatory Peritoneal Dialysis (CAPD) in patients undergoing hemodialysis, and to determine the description of knowledge of patients undergoing hemodialysis at Imelda Indonesian Workers General Hospital regarding Continuous Ambulatory Peritoneal Dialysis (CAPD). This study used a quantitative descriptive research design. The study involved two variables: the independent variable, which was knowledge, and the dependent variable, which was Continuous Ambulatory Peritoneal Dialysis (CAPD). The sampling technique used in this study was purposive sampling, where samples were selected based on predetermined criteria. The total sample consisted of 60 respondents. The results of the Chi-Square test presented in the table showed a p-value of 0.004. This means that the probability value is less than the level of significance (α = 0.05), so Ha is accepted and H0 is rejected. Therefore, it can be concluded that there is a significant relationship between the knowledge of patients undergoing hemodialysis and CAPD.